2019
DOI: 10.3390/ijerph16244919
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variations of Trace Metals and Their Complexation Behavior with DOM in the Water of Dianchi Lake, China

Abstract: The dynamics of trace metals and the complexation behavior related to organic matter in the interface between water and sediment would influence water quality and evolution in the lake system. This study characterized the distribution of trace metals and the optical properties of dissolved organic matter (DOM) on the surface, and the underlying and pore water of Dianchi Lake (DC) to understand the origin of metals and complexation mechanisms to DOM. Some species of trace metals were detected and Al, Ti, Fe, Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…However, the studies were lacking the molecular weight effect on the ratio difference in the soil solutions. In an aquatic environment, the [Cu]/[DOC] ratios of bulk DOM had been reported by some researchers [16,29,30,32,33]. The ratios were positively correlated with aromaticity for natural water DOM [29,32].…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…However, the studies were lacking the molecular weight effect on the ratio difference in the soil solutions. In an aquatic environment, the [Cu]/[DOC] ratios of bulk DOM had been reported by some researchers [16,29,30,32,33]. The ratios were positively correlated with aromaticity for natural water DOM [29,32].…”
Section: Introductionmentioning
confidence: 71%
“…The copper and organic matter binding affinity, [Cu]/[DOC] ratio, was used to understand the variation in the binding ability of copper to DOM/WEOM [10,11,16,[29][30][31][32][33]. Table 4 lists the [Cu]/[DOC] ratios of bulk and size-fractioned AEOM solutions for each site.…”
Section: Cu and Aeom Binding Affinity [Cu]/[doc] Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…DOM has a significant impact on the migration and transformation of Mn in groundwater. Yi et al (2019) analyzed the relationship between DOM and heavy metals in the water of Dianchi Lake and found that DOM and heavy metals have complex effects. Hongxia et al (2014) using excitationemission matrix fluorescence spectroscopy (EEM) was combined with parallel factor analysis to analyze the fluorescence components of DOM in surface water of rare earth mining areas, finding there was a significant positive correlation between protein-like components and rare earth metals.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%